Use of personal mobile technologies for peer-based assessment of stress: a systematic literature review - Bellanger, Antoine; Matias, Igor; Wac, Katarzyna (EAI Endorsed Transactions on Pervasive Health and Technology, 2025)
The use of personal mobile technologies has grown in recent years, providing a method for collecting high-frequency and high-quality data on human behaviors and states, amongst the others, on stress levels. Mobile technologies can play a significant role in peer-based stress assessment, particularly in e-mental health and well-being. It is accessible, convenient, and reliable compared to traditional self-report methods, making it a popular choice for collecting data. This systematic literature review aimed to explore the use of mobile technologies for peer-based assessment of stress. We analyzed existing literature to understand how mobile technologies have been used to assess stress levels through peer feedback—from relatives, friends, or others with close and daily contact with the individual. The results of the review showed that mobile technologies have the potential to be a valuable tool for peer-based stress assessment, as they can provide real-time and convenient data collection. However, although its popularity has grown in recent years, it is worth noting that the use of paper and pen questionnaires has remained prevalent in peer-based stress assessment over the last decade. This indicates that there is still a need for further exploration and evaluation of the benefits and limitations of both methods.
Keywords: Mobile technologies; peers; stress; systematic literature review; behaviors; human stares